Percutaneous Auricular Vagus Nerve Stimulation Reduces Inflammation in Critical Covid-19 Patients - Seitz, Tamara; Szeles, József Constantin; Kitzberger, Reinhard; Holbik, Johannes; Grieb, Alexander; Wolf, Hermann; Akyaman, Hüseyin; Lucny, Felix; Tychera, Alexander; Neuhold, Stephanie; Zoufaly, Alexander; Wenisch, Christoph; et al. (Frontiers in Physiology, 2022)
Covid-19 is an infectious disease associated with cytokine storms and derailed sympatho-vagal balance leading to respiratory distress, hypoxemia and cardiovascular damage. We applied the auricular vagus nerve stimulation (aVNS) to modulate the parasympathetic nervous system, activate the associated anti-inflammatory pathways, and reestablish the abnormal sympatho-vagal balance. aVNS is performed percutaneously using miniature needle electrodes in ear regions innervated by the auricular vagus nerve. In terms of a randomized prospective study, chronic aVNS is started in critical, but not yet ventilated Covid-19 patients during their stay at the intensive care unit. The results show decreased pro-inflammatory parameters, e.g. a reduction of CRP levels by 32% after one day of aVNS and 80% over 7 days (from the mean 151.9 mg/dl to 31.5 mg/dl) or similarly a reduction of TNFalpha levels by 58.1% over 7 days (from a mean 19.3 pg/ml to 8.1 pg/ml) and coagulation parameters, e.g. reduction of DDIMER levels by 66% over 7 days (from a mean 4.5 µg/ml to 1.5 µg/ml) and increased anti-inflammatory parameters, e.g. an increase of IL-10 levels by 66% over 7 days (from the mean 2.7 pg/ml to 7 pg/ml) over the aVNS duration without collateral effects. aVNS proved to be a safe clinical procedure and could effectively supplement treatment of critical Covid-19 patients while preventing devastating over-inflammation.